Photodynamic Therapy for Condyloma Acuminatum and Cervical Intraepithelial Neoplasia Grade I in a Young Female Patient with Systemic Lupus Erythematosus: A Case Report - Zhang N; Ge H; Chen X; Ye T; Shi W; Wang M (Dove Medical Press, 2024)
Na Zhang,* Hongping Ge,* Xinru Chen, Tianhui Ye, Weikang Shi, Meiyan Wang Department of Dermatology, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, People's Republic of China*These authors contributed equally to this workCorrespondence: Meiyan Wang, Email wmy196501@163.comAbstract: Condyloma acuminatum (CA), commonly known as anogenital warts, is a prevalent sexually transmitted disease primarily caused by low risk human papillomavirus (HPV) types 6 and 11. This case report outlines the successful use of photodynamic therapy (PDT) to treat extensive condyloma acuminatum in a young female patient with systemic lupus erythematosus (SLE) undergoing immunosuppressive treatment. The patient also had cervical intraepithelial neoplasia grade I. Carbon dioxide laser treatment were initially used to remove some surface warts, followed by PDT, resulting in satisfactory outcomes. After seven sessions, the warty growths were successfully removed. Interdisciplinary collaboration, involving rheumatology, gynecology, and dermatology, facilitated comprehensive management. This case highlights the efficacy and safety of PDT in treating condyloma acuminatum and suggests its potential as an alternative treatment for young SLE patients with similar conditions.Keywords: condyloma acuminatum, photodynamic therapy, systemic lupus erythematosus